Spatial genetic structure and body size divergence in endangered Gymnogobius isaza in ancient Lake Biwa. (4th July 2018) - Nakazawa, Takefumi; Liu, Shang-Yin Vanson; Sakai, Yoichiro; Araki, Kiwako S.; Tsai, Cheng-Han; Okuda, Noboru
Abstract: Gymnogobius isaza is a freshwater goby endemic to ancient Lake Biwa, the largest lake in Japan. The species is now listed as 'Critically Endangered' in the Red Data Book of Japan. Nevertheless, it remains subject to fishing without any specific management strategies. Previous studies using mitochondrial DNA markers showed that this fish species has two cryptic lineages. However, little is known about spatial genetic structure and ecological differences across the broad lakescape. In this study, we collected fish samples at nine locations along the lakeshore during the breeding season and tested for the presence of spatial heterogeneity in the lineage's composition while measuring body size as the most fundamental biological trait. The results showed that the major lineage dominated all the sampling locations whereas the minor lineage consisted of only 11% (16/143) of samples. Furthermore, although their spatial distributions overlapped (i.e. the two lineages may be well mixed), we found it possible that the minor lineage may have a potentially narrower distribution than the major lineage. In addition, we found that the two lineages differ in body size; specifically, the minor lineage is smaller in size. From the viewpoint of genetic diversity conservation and sustainable resource use, this fish should be managed as two genetic stocks and spatial and/or body size-based fishery management is desirable, with particular attention to the minor (smaller sized) lineage.